Rancang Bangun Sistem Informasi Pada Kantor Desa Sebagai Media Pengajuan Surat Dengan Metode Waterfall - Dunga Triandri; Istikoma; Sucipto (Penerbit Jurnal Indonesia, 2025)
The Tumuk Manggis Village Government, Sambas District, Sambas Regency still provides manual letter processing services, which require people to come directly to the Village office. This is considered inefficient because the process takes a long time, coupled with the lack of human resources and mastery of technology by Village employees. In addition, on average, employees at the village office are rarely there and also operational hours are not opened according to the adjusted time. To overcome this problem, a website-based information system is needed that can facilitate online letter submission. This study aims to design and build a letter submission information system using the waterfall method, which includes the stages of needs analysis, design, implementation, testing, and maintenance. The waterfall method was chosen because the process is structured and carried out in stages so that it is easy to develop the system according to what the user wants. Testing was carried out using black box testing to ensure that the system being built is seen and confirmed. The results of the UAT test obtained with an average value of 90.2% which is included in the Strongly Agree category. The results of this study are a website-based system that is expected to be able to accelerate and streamline the letter submission process, so that services become more structured and effective for the people of Tumuk Manggis Village